PRIMARY CLASS TEXTBOOKS IN A NEW EDITION - Xolboeva Gulnora Anorboevna (Journals Park Publishing, 2023)
In this article, by using the "4K" model (critical thinking, creativity, collaboration, communication) in the new generation textbooks created for grades 1-4 in improving the quality and efficiency of primary education, students' critical thinking, creative approach, teamwork it is thought that it is aimed at developing working and communication skills . After the adoption of the Law "On Education" of the Republic of Uzbekistan, extensive positive changes are being implemented in the education system, particularly in primary education.
Keywords: critical thinking, creativity, collaboration, communication